Education, Training, and Academic Experience of Newly Hired, First-Time Pharmacy Faculty Members - Wanat, Matthew A. (American Journal of Pharmaceutical Education, 2014)
Objective. To describe the education, training, and academic experiences of newly hired faculty members at US colleges and schools of pharmacy during the 2012-2013 academic year. Methods. A survey regarding education, training, and academic experiences was conducted of all first-time faculty members at US colleges and schools of pharmacy hired during the 2012-2013 academic year. Results. Pharmacy practice faculty members accounted for the majority (68.2%) of new hires. Ambulatory care was the most common pharmacy specialty position (29.8%). Most new faculty members had a doctor of pharmacy (PharmD) as their terminal degree (74.8%), and 88.3% of pharmacy practice faculty members completed a residency. Of new faculty members who responded to the survey, 102 (67.5%) had at least 3 prior academic teaching, precepting, or research experiences. Conclusion. New faculty members were hired most frequently for clinical faculty positions at the assistant professor level and most frequently in the specialty of ambulatory care. Prior academic experience included precepting pharmacy students, facilitating small discussions, and guest lecturing.